Diversity of Soil Arthropods in Three Elevations of Coffee Plantations, Tebat Pulau Village, Bermani Ulu, Rejang Lebong District - Maulana Insanul Kamil; Elsa Lolita Putri; Willi Novrian; Hefri Oktoyoki; Hariz Eko Wibowo; Rihan Ifebri; Ariffatchur Fauzi; Agustin Zarkani; Fitri Yuwita (Badan Penerbitan Fakultas Pertanian (BPFP), 2023)
Coffee is a leading commodity in Bengkulu Province, whose production still needs to be improved. One of the supporting factors for coffee fruit production is the existence of a good soil arthropod ecosystem. Information regarding the diversity of soil arthropods can be considered in evaluating coffee plants' health. This research aims to obtain initial data on the diversity of soil arthropods and their role in central coffee plantations in Tebat Pulau Village, Bermani Ulu District, Rejang Lebong Regency. This research began with taking soil samples from productive coffee plantations. The type of coffee plant sampled was robusta coffee at an altitude of 900, 1000, and 1100 meters above sea level. Next, the soil taken is placed in the bottom funnel. Arthropods obtained from the Berlesse funnel were identified and counted. The results of counting arthropods are used to calculate diversity, dominance, and evenness index numbers. The results show moderate variability in the three types of elevation: low dominance, high evenness. Research also shows that the highest number of arthropods is found at an altitude of 900 m, and the most common type is acarina.